2008
DOI: 10.1159/000170890
|View full text |Cite
|
Sign up to set email alerts
|

Folate, Vitamin B<sub>12</sub> and Homocysteine Status in Women of Childbearing Age: Baseline Data of Folic Acid Wheat Flour Fortification in Iran

Abstract: Background: Folic acid fortification implemented mandatorily in many countries has been associated with significant increase in blood folate concentrations and reduction in the prevalence of neural tube defects. However, there are controversial findings on the probability of vitamin B12 deficiency being masked in the population after folic acid fortification. Baseline data on folate and vitamin B12 status are necessary before mandatory flour fortification is implemented. Objectives: To as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 62 publications
5
27
0
Order By: Relevance
“…Methylenetetrahydrofolate reductase, cystathionine condensing enzyme, and methionine synthetase are important metabolic enzymes in methionine metabolism, while FA and Vit B12 are essential prosthetic groups. FA and/or Vit B12 deficiency is associated with hyperhomocysteinemia (Abdollahi et al, 2008). Our study indicated that FA and Vit B12 levels in the maternal blood were negatively correlated with Hcy content, confirming that FA and/or Vit B12 deficiency is associated with hyperhomocysteinemia.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Methylenetetrahydrofolate reductase, cystathionine condensing enzyme, and methionine synthetase are important metabolic enzymes in methionine metabolism, while FA and Vit B12 are essential prosthetic groups. FA and/or Vit B12 deficiency is associated with hyperhomocysteinemia (Abdollahi et al, 2008). Our study indicated that FA and Vit B12 levels in the maternal blood were negatively correlated with Hcy content, confirming that FA and/or Vit B12 deficiency is associated with hyperhomocysteinemia.…”
Section: Discussionsupporting
confidence: 69%
“…Insufficient nutrients may lead to FA and Vit B12 deficiencies in the mothers, and thus affect the fetuses as well. In addition, FA and Vit B12 deficiencies can lead to the conversion of homocysteine (Hcy) to methionine, resulting in homocystinemia (Abdollahi et al, 2008). High Hcy content can be damaging to vascular structures and functions, resulting in insufficient blood perfusion to the fetus, and abnormal fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…Our results were comparable with those of Abdolahi et al's study, which reported a folate deficiency in 14.3% of the women of the childbearing ages in Gorgan before a folic acid fortification was implemented [6]. Our study was done six months after a flour fortification with folic acid and iron was given.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, a vitamin B12 deficiency was detected in 32% of the subjects, which was reported to be 22.7% in the northern Iran before the flour fortification with folic acid implemented [6]. A vitamin B12 deficiency was reported in 39.4% women of the childbearing ages in Lebanon [7], in 21.4% women in Korea [9] and in 13 % women in Bangladesh [8].…”
Section: Discussionmentioning
confidence: 49%
“…Folic acid and vitamin B 12 as two vital regulators play an important role in regulating the metabolic process of Hcy [27,28]. Folic acid and vitamin B 12 deficiency would result in elevated level of Hcy [29,30].…”
Section: Discussionmentioning
confidence: 99%